Orientación vocacional para la inclusión laboral de los estudiantes con NEE - Sornoza Espinoza, Jorge David (2022)
Vocational guidance is an important element during the school education of any person, since it will help them to know themselves, discover their potentialities, recognize their interests and finally, make the right decisions that contribute to following the best path in adult life; for those with a moderate intellectual disability, this is essential and could make a difference in the processes of labor inclusion, since these students deserve a process of orientation and assertive follow-up, with which it is possible to influence them to acquire better skills for compete in the workplace. Due to the importance that this has, it was decided to carry out this research work, which was focused on analyzing the incidence of vocational guidance in the labor insertion of students with special educational needs associated with moderate intellectual disability in the "Fiscal Educational Unit Specialized La Floresta” of the city of Guayaquil. For this, a mixed investigation was carried out, in which teachers, DECE representatives, students and legal representatives served as a sample, to whom surveys and interviews were applied, the results of which showed that it is necessary to implement the vocational orientation program and professional in the institution, for what is proposed as an alternative solution, a guide to teaching strategies to provide vocational guidance to students with moderate intellectual disabilities.